Effect of Multilaminate Small Intestinal Submucosa as a Barrier Membrane on Bone Formation in a Rabbit Mandible Defect Model. (19th June 2018) - Wu, Weiyi; Li, Bowen; Liu, Yuhua; Wang, Xinzhi; Tang, Lin
Abstract : A barrier membrane (BM) is essential for guided bone regeneration (GBR) procedures. Absorbable BMs based on collagen have been widely applied clinically due to their excellent biocompatibility. The extracellular matrix (ECM) provides certain advantages that can compensate for the rapid degradation and insufficient mechanical strength of pure collagen membrane due to the porous scaffold structure. Recently, small intestinal submucosa (SIS), one of the most widely used ECM materials, has drawn much attention in bone tissue engineering. In this study, we adopted multilaminate SIS (mSIS) as a BM and evaluated its in vivo and in vitro properties. mSIS exhibited a multilaminate structure with a smooth upper surface and a significantly coarser bottom layer according to microscopic observation. Tensile strength was 13.10 ± 2.56 MPa. In in vivo experiments, we selected a rabbit mandibular defect model and subcutaneous implantation to compare osteogenesis and biodegradation properties with one of the most commonly used commercial collagen membranes. mSIS was retained for up to 3 months and demonstrated longer biodegradation time than commercial collagen membrane. Quantification of bone regeneration revealed significant differences in each group. Micro-computed tomography (micro-CT) revealed that the quantity and maturity of bones in the mSIS group were significantly higher than those in the blank control group ( P < 0.05) and were similar to those in a commercial collagen membrane group ( P > 0.05) at 4 and 12 weeks after surgery. Hematoxylin and eosin staining revealed large amounts of mature lamellar bone at 12 weeks in mSIS and commercial collagen membrane groups. Therefore, we conclude that mSIS has potential as a future biocompatible BM in GBR procedures.